(untitled) (Global Journal of Human-Social Science, 2023)
The systematic review and meta-analysis presented in this study aim to provide an overview of the literature on the meaning of life and existential vacuum within the contemporary field of psychology investigating the approaches and methodologies employed in this area from 2000 to 2023 The review encompassed five databases including CAPES portal APA PsycArticles SCOPUS SCIELO and PEPSIC utilizing combinations of descriptors such as existential vacuum and meaning of life along with related terms in conjunction with mental health and clinical psychology both in English and their respective Portuguese counterparts The inclusion criteria involved selecting articles that centered on the themes of existential vacuum or meaning of life as the primary focus published between 2000 and 2023 and written in English Spanish or Portuguese A total of 671 articles were initially identified with 264 meeting the inclusion criteria and subsequently subjected to meta- analysis These articles were categorized into various approaches 191 employed quantitative methods 46 were theoretical qualitative 17 were empirical qualitative 7 used mixed methods and 3 focused on interventions